Above-floor tube-and-plate radiant floor model development and validation. Issue 4 (4th July 2018) - Brideau, S.A.; Beausoleil-Morrison, I.; Kummert, M.
Abstract : While some building energy simulation tools include dedicated models to represent thermally massive embedded-tubes radiant floor systems, there are no models available for lightweight above-floor tube-and-plate (AFTP) systems. AFTP systems consist of a grooved wooden subfloor (or high density insulation layer), and conductive fin. This paper discusses the development of a transient AFTP radiant floor model and its implementation into ESP-r. This AFTP radiant floor model uses the general approach of the existing embedded-tube model in ESP-r and combines an analytical model of the tube with a two-dimensional finite difference model of the top layers of the floor construction. The new AFTP radiant floor model was found to compare closely with a transient two-dimensional finite element analysis model. Additionally, a full-scale transient experiment was conducted to empirically validate the model. The new model's predictions were found to be in close agreement with the measurements from this experiment.